School-based professionals’ experiences in supporting autistic learners in feminised settings - Nettie N. Ndou-Chikwena; Maximus M. Sefotho (South African Journal of Childhood Education, 2025)
Background: School-based professionals play a crucial role in supporting autistic learners, with teachers and occupational therapists being primary implementers of education and health policies. The support context reflects cultural feminist principles, as women professionals predominantly provide immediate support in schools.